The formation processes and functions of slang words among American youth in Casey McQuiston’s Red, White & Royal Blue (2019) - Friska Amelia Novrianti; Dyah Kristyowati; Resty Widya Kurniasari (Universitas Pakuan, 2025)
This study explores the word formation processes and social functions of slang used by American youth in Red, White & Royal Blue by Casey McQuiston. Using a descriptive qualitative approach and Yule’s (2006) theory of morphology, 35 slang expressions were identified and 10 were analyzed in depth. The findings show that slang in the novel emerges from processes like clipping, acronyms, compounding, and derivation. These expressions not only demonstrate linguistic creativity but also convey social identity, emotional intimacy, and solidarity. This study contributes to the understanding of slang as a reflection of youth culture in contemporary literature.